Highly concentrated emulsion with a cubic liquid crystal as the external phase: characterization and obtaining of meso/macroporous material - Santamaría, E.; Cortés, M.; Maestro, A.; Porras, M.; Gutiérrez, J. M.; González, C. (Journal of Nepal Chemical Society, 2013)
High internal phase ratio emulsions (HIPRE) or highly concentrated emulsions are characterized by their large internal phase volume.The nature and concentration of surfactant affects several features of the final emulsion, such as stability, droplet size and structure of the external phase. Therefore, an ordered external mesophase (structure of liquid crystal) can be obtained. The present work studies the influence of composition and preparation variables on the final properties of HIPRE with an external phase formed by a bicontinuous cubic liquid crystal. The studied outputs variables were droplet size, stability and rheological parameters as yield stress, viscosity at a fixed shear rate and the plateau value of the storage modulus. O/W HIPREs were prepared with a decane/brij 35/water system. Once the emulsions were characterized the meso/macroporous material was obtained. In order to prepare the materials, the emulsions were formed by incorporating the catalyst of the reaction (HCl) in the continuous phase. When the emulsions were formed, tetraethylorthosilicate (TEOS) was added as a silica source In order to optimize the production process a study of reutilization and recovery of some of the raw materials (i.e: the surfactant and the EtOH used) was done. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9374 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 87-96 Uploaded date: 12/19/2013